Circularly polarized mimo array antenna for 5.8 Ghz point-to-point communication - Mohd Khairul Azhar Nayan (School of Computer and Communication Engineering, 2016)
The project first starts with the design of a single element circular polarization antenna. This circular polarization feature is enabled by using truncated edged technique at Top-right and Bottom-left of the rectangular patch antenna and 90° physical phased shifter that are fed using coax feeding technique. Several variations of this antenna will also design, mainly with the objectives of resulting in a compact CP structure. Next, each variation of the optimized single element antenna will then be duplicated into an array form of 2x2 elements. This is to enable high gain CP antenna from each variation. Finally, two sets of each array will be used to form the MIMO feature.